The stoichiometric legacy of fire regime regulates the roles of micro‐organisms and invertebrates in decomposition - Orpheus M. Butler; Tom Lewis; Mehran Rezaei Rashti; Sarah C. Maunsell; James J. Elser; Chengrong Chen (Ecology, 2019)
Decadal‐scale increases in fire frequency have the potential to deplete ecosystems of essential nutrients and consequently impede nutrient‐limited biological processes via stoichiometric imbalance. Decomposition, a fundamental ecosystem function and strong driver of future fire occurrence, is highly sensitive to nutrient availability and is, therefore, particularly important in this context. Here we show that 40 yr of quadrennial (4yB) and biennial (2yB) prescribed burning result in severely P‐ and N‐depleted litter stoichiometry, respectively, relative to fire exclusion. These effects exacerbated the nutrient limitation of microbial activities, constraining litter decomposition by 42.1% (4yB) and 23.6% (2yB) relative to unburned areas. However, invertebrate‐driven decomposition largely compensated for the diminished capacity of micro‐organisms under 4yB, suggesting that invertebrates could have an important stabilizing influence in fire‐affected ecosystems. This effect was strongly positively coupled with the strength of microbial P‐limitation and was not obviously or directly driven by fire regime‐induced changes in invertebrate community assemblage. Together, our results reveal that high‐frequency fire regimes promote nutrient‐poor, carbon‐rich ecosystem stoichiometry and, in doing so, disrupt ecosystem processes and modify the relative functionality of micro‐organisms and invertebrates.